La inteligencia emocional y su relación con la lecto-escritura de los niños y niñas del primer grado de educación general básica de la escuela “Gabriela mistral nº 1” del cantón Catamayo, provincia de Loja, periodo lectivo 2013 – 2014”. Lineamientos propositivos - Martínez Mendoza, Paola Estefania (2015)
This work developed is limited in the analysis of “LA INTELIGENCIA EMOCIONAL Y SU RELACIÓN CON LA LECTO-ESCRITURA DE LOS NIÑOS Y NIÑAS DEL PRIMER GRADO DE EDUCACIÓN GENERAL BÁSICA DE LA ESCUELA “GABRIELA MISTRAL Nº 1” DEL CANTÓN CATAMAYO, PROVINCIA DE LOJA, PERIODO LECTIVO 2013 – 2014”. LINEAMIENTOS PROPOSITIVOS. The central problem ¿How Emotional Intelligence is related the Literacy of Children First Grade General Education Basic School "Gabriela Mistral No. 1" of the Catamayo town, Loja Province, academic year 2013 - 2014? The general objective raised in this research was: To show the relationship of emotional intelligence with the Literacy of Children First Degree General Basic Education of "Gabriela Mistral No. 1" School of Catamayo town province of Loja, academic year 2013-2014. The methods used were: Scientist, Synthetic, inductive, deductive and statistical model, the same that served effectively help to achieve the proposed goal. Test of Emotional Competence Emotional Intelligence to determine which children have instruments such as was applied. Testing also Basics to assess literacy. Information obtained through the application of the instruments provided for that purpose, it was possible to conclude: through the Test of emotional skills: self-knowledge 60% Activity 2 can recognize their abilities; on the other hand 40% do not recognize their capabilities. Autonomy In 58% of the activity 1 assumes responsibilities according to their age and 42% not assumed. In listening 58% Activity 2 good listeners paying attention to their peers, and 42% do not. Positive Thinking in 65% of the activity 2 has a thought of optimism and 35% have a negative thought. Conflict Resolution 65% Activity 2 have a positive attitude towards conflicts and 35% do not. In the test to evaluate the Basic Literacy functions, it was concluded that 69% have a successful literacy; on the other hand they have a 31% literacy unsatisfactory.